BLOOD PLASMA TRACE ELEMENTS IN REPEAT BREEDING MEHSANA BUFFALOES - KAPADIYA, F M; SIDDIQUEE, G M (The Indian Journal of Animal Reproduction, 2023)
Blood plasma trace minerals analysis indicated that the levels of iron, copper, cobalt, zinc and manganesewere comparatively higher in antibiotics (Cephalexin or Ciprofloxacin+ Tinidazole) treated Groups-I and II as comparedto untreated control Group of repeat breeding buffaloes (n=6 each) whereas cobalt and manganese were significantlyhigher in treated Groups-I.
Keywords: Trace minerals; Repeat breeder; Buffalo